Principles of international environmental law - Sands, Philippe , 1960-; Fabra Aguilar, Adriana; MacKenzie, Ruth , 1964-; Peel, Jacqueline , 1974- (Cambridge : Cambridge University Press, 2012)
The third edition of this classic text offers comprehensive and critical commentary on international environmental law
1. The legal and institutional framework -- 2. Principles and rules establishing standards -- 3. Techniques for implementing international principles and rules -- 4. Linkage of international environmental law and other areas of international law
Includes index
Keywords: Environmental law, International